Management of relapsed/refractory mantle cell lymphoma: a review of current therapeutic strategies. Issue 5 (May 2014) - Zaja, Francesco; Federico, Massimo; Vitolo, Umberto; Zinzani, Pier Luigi
Abstract Despite recent advances in therapeutic strategies, a large proportion of patients with mantle cell lymphoma (MCL) experience progression after first-line treatment. Several attempts have been made to assess the role of different therapies for the treatment of patients with relapsed/refractory mantle cell lymphoma; however, a consensus on the optimal therapeutic strategy for each individual patient has not been reached. Overall, clinical evidence from phase II studies shows that high-dose cytarabine containing regimens, stem cell transplant and different biological agents all have promising activity with acceptable safety profiles. Therefore, these therapies can represent suitable treatment options for patients with relapsed/refractory MCL. Among different biological agents, at present only temsirolimus has been tested in a phase III study. This review considers available evidence on the management of relapsed/refractory MCL as discussed during a consensus meeting on the current treatment strategies for MCL.